An Expenditure on Health and Expectancy of Life Dynamics in Nepal: An Analysis With Uneven Linearity - Pokhrel, Aditya; Adhikari, Renisha (Economic Review of Nepal, 2024)
Using yearly time-series data from 1995-2020, this research explores the asymmetric link between public health expenditure and life expectancy. Zivot unit-root testing and NARDL co-integration analysis were both used in this study's econometric approach; the former allowed for a single significant break in the model, while the latter took into account the presence of the structural break and analyzed the long-run asymmetric relationship. The study's findings show that public health spending as a percentage of GDP had a co-integrating connection, which means that negative shocks to this spending might lead to an increase in it and, in turn, a longer life expectancy. When the economy experiences negative shocks, not the positive ones, the government's response has to be proactive in raising health expenditure. Policymakers can use the study's findings as a reference for crafting a public health expenditure policy. This study has also made a novel contribution by applying nonlinearity and structural break unit-root tests, which were not tested in previous studies, to fill in the geographical gap that those studies had.